A Critical Edition and Philological Analysis of the Text of Isa 46–48 on the Basis of the Coptic Manuscript sa 52 (M 568) and other Coptic Manuscripts in the Sahidic Dialect and the Greek Text of the Septuagint - Bąk, Tomasz Bartłomiej (The Biblical Annals, 2021)
The article constitutes a critical edition and a philological analysis of the text of Isa 46-48, based on the Coptic manuscript sa 52 and other available manuscripts in the Sahidic dialect. The first part provides general information on this fragment of the codex sa 52 (M 568), which includes the text being elaborated. This is followed by a list and a brief description of the remaining manuscripts, containing at least some verses from Isa 46-48. The most significant part of the article is the presentation of the Coptic text (in the Sahidic dialect) as well as its translation into English. The differences noted between the Sahidic text and the Greek Septuagint, on which the Coptic translation is based, are presented in a tabular form. It includes, i.a., additions and omissions in the Coptic translation, lexical changes and semantic differences. The last part of the article is devoted to more difficult philological issues, observed either in the Coptic text itself or in its relation to the Greek text LXX. Particularly noteworthy are those verses of Isa 46-48, which appear only in the manuscript sa 52.2 and have not been published anywhere so far.